Jøder i Labyrinten - Jens Baggesen om ghettoen i Frankfurt am Main - Harbsmeier, Michael (Rambam. Tidsskrift for jødisk kultur og forskning, 2016)
Jews in the Labyrinth One of the most famous passages of the novel Labyrinten by the Danish-German author Jens Baggesen from 1792/3 deals with the Judengasse in Frankfurt am Main. The novel itself is very much inspired by Laurence Sterne’s Sentimental Journey, but in his account of his visit to the ghetto in 1789, Baggesen has not only painted a most moving, almost ethnographic image of the daily life and the appalling living conditions in the ghetto, but also produced one of the strongest and most enthusiastic calls for the recognition of civil rights and Jewish emancipations of the time. After a presentation of Baggesen’s portraits of Jews in his novel, this article compares his account to a whole series of sometimes strikingly anti-Semitic predecessors.